Gambaran Health Literacy, Pengetahuan, Kepercayaan, Sikap, Dan Perilaku Oleh Pemilik, Karyawan, Pengunjung Dalam Mencegah Covid-19 Di KMS Jember - Winarso S; Irfiah Irfiah; Styantari Y; Soraya A; Andari K; Wahyudi A Z (Multidisciplinary Journal, 2020)
Corona Virus Disease 2019 or COVID-19 was announced as pandemic by WHO by the end of 2020. The pandemic, a breakout around the globe, can slow down or paralyze all activities in every level of society. Several efforts have been done to avoid COVID 19 breakout including mask wearing, hand washing, sanitizing, or 1 meter social distancing between people in public places such as restaurants. This residency is aimed at identifying and describing the health literacy, knowledge, trust, attitude and behavior of the restaurant owner, employee and visitors to prevent COVID-19. This research applied descriptive method with respondents including the owner, 30 employees and 30 visitors using Google form as the instruments. The results reveals that healthy literacy media used by the owner, employees and visitors are electronic media and only small numbers of them were following the development of COVID 19 case. Owner’s knowledge is good but there is gap between owner, employees and visitors in terms of knowledge on general symptoms, effects and contagious transmission of the disease as well as highly risk infected people. The trust identification shows that the owner believes COVID 19 does not airborne but the employees and visitors do. Meanwhile, attitude and behavior identification shows good and fair indicators for the employees and visitors in terms of social distancing and well-worn mask. Owner’s attitude is considered good in terms of providing all protocol necessity to prevent COVID19. Owner’s behavior during the COVID-19 pandemic are considered good by initiating health protocols by applying the standardized operational procedures. Furthermore, the behavior of employees are mostly good in terms of health protocol application to prevent COVID-19. On the other hand, visitors are basically good but several of them still touched their eyes, nose and other parts of their face. In conclusion, the various answers from respondents (owners, employees and visitors) are varied in terms of their knowledge, health literacy, trust, attitude and behavior. Keywords: COVID-19, KMS, owner, employee, visitors